Capturing digital data with handheld devices to determine the redox regime, lithology, and provenance of siliciclastic sediments and residual deposits—a review and field manual - Dill, Harald G.; Buzatu, Andrei; Maftei, Andreea Elena (Arabian journal of geosciences, 2017)
Geomagnetic (magnetic susceptibility), geoelectrical (resistivity and conductivity, self-potential/SP, induced polarization/IP), and radiometric measurements (gamma radiation of K, U, and Th) are well adapted to the needs and wants of geoscientists and exploration geologists, in particular, who widely use them in wireline tools and for ground surveys. Miniaturization of technical components resulted in the production of handheld devices which enable field geologists to an improving of the mineralogical and chemical database and the efficiency of the routine work in the field or at a drill site. The tools and devices used by a field geologist are categorized and presented in a tripartite set. The tools for routine field work with “hammer and laptop” belong to the A-level kit. The handheld devices under consideration constitute an intermediate level (B-level) to enhance the mineralogical and chemical database using physical methods. More advanced level applications make use of short-wave infra-red mineral analyzers or portable X-ray fluorescence devices (C-level). Handheld tools are designed for one-dimensional (cross-sectioning) and two-dimensional (mapping) surveys as well as drill core and cuttings examinations during terrain analysis. They can be operated in foot-borne surveys by one field geologist and the obtained data interpreted without an exuberant computing capacity. In the present overview, siliciclastic rocks and residual deposits have been singled out for their good response to the afore-mentioned methods. Their practical use is demonstrated by means of some case histories, each standing for a particular sedimentary lithology and discussed in combination with similar applications from literature: mixed-type (calcareous) siliciclastic rocks from Mesozoic–Cenozoic basins, SE Germany; residual argillaceous/kaolin deposits on top of granites of the Variscan basement, SE Germany; Neogene red-bed sediments from the promontory of the Tien Shan, East Uzbekistan; and Cretaceous gray-bed sediments with coal seams from the Baganuur basin, Central Mongolia. Cobweb diagrams, histograms, ternary diagrams, simple x - y plots and x - y plots in combination with spider diagrams have proved to be the most suitable ways when it comes to combine the data obtained from various methods and to illustrate these results for further interpretation on screen. The geophysical methods are discussed as to their strong and weak points to cater for a solution in three important subject matters of applied and genetic sedimentology: (1) constraining the redox regime, (2) determination of the lithology and mineralogy, (3) and provenance analysis and lithostratigraphy. Magnetic methods have proved to be useful for all objectives (1, 2, and 3), gamma spectrometry can successfully be applied for objectives 1 and 2, and micro-resistivity contributes significantly to solutions of objective 2. Magnetic and gamma spectrometric methods do not need any direct contact with the sedimentary rocks and therefore can be correlated with equivalent airborne surveys and are less depending on the wetability of the substrate and climate than the geoelectrical methods under study. The final goal of this review is to create a matrix of applicability of the methods and enable the field geologist to select the most suitable type of geophysical measurement or combination of tools for a solution to one of the three issues as a function of the sediment types under study.